Effect of cable corrosion on nonlinear elastic stability of girder in Cable-Stayed bridges with floating systems. (March 2022) - Lu, Wengao; He, Zheng
Highlights: An investigation of the influence of cable corrosion on nonlinear elastic stability of long-span cable-stayed bridges based on the energy method. The beam on elastic foundation model is applied to evaluate the number of half-waves through the weakest section in a girder of cable-stayed bridge. The feasibility and reasonability of the proposed procedures are validated by two ideal beams and a real long-span cable-stayed bridge with assumed corrosion scenarios. Abstract: This paper presents an investigation of the influence of cable corrosion on the nonlinear elastic stability of long-span cable-stayed bridges based on the energy method and the theory of the beam on elastic foundation (TBEF). The corrosion-induced fluctuations in vertical support rigidity and the non-uniform distributions of axial forces between girder segments are considered by a discretized model based on the energy method. The classical TBEF model is applied to evaluate the number of half-waves through the identification of the weakest section in a girder, prior to the numerical solution to the buckling eigenvalue equations derived from the discretized model. The feasibility and reasonability of the proposed procedures are validated by two ideal beams and a case study on a real long-span cable-stayed bridge with assumed corrosion scenarios, through the comparison with the results from elastic finite element analysis considering geometric nonlinearities. The case study has indicated that cable corrosion exerts a significant influence on critical buckling load, exhibiting an approximate linear relation with corrosion ratio. However, corrosion does not seem to put a significant effect on the number of half-waves of buckling mode of the girder. The possibility of failure modes switch is found to depend primarily on the spacing of cables and the depth of girder. Cable-stayed bridges having densely distributed cables and relatively shallow girder possess a higher possibility of failure modes switch when severe corrosion takes place.